2021
DOI: 10.3390/children8060491
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Relationship between Couple Dyadic Adjustment and Family Health

Abstract: The importance of family functioning in the development of child and adult psychopathology has been widely studied. However, the relationship between partners’ adjustment and family health is less studied. This paper aims to describe and summarize research that analyzes the relationship between partners’ adjustment and family health. A systematic review was conducted in the PubMed, PsycINFO, Scopus, Lilacs, Psicodoc, Cinahl, and Jstor databases. Inclusion criteria were as follows: articles published from 2012 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 57 publications
(121 reference statements)
0
9
0
1
Order By: Relevance
“…2 Resilience, defined as the ability to overcome challenging obstacles and successfully cope with stressful events 45 is a contributing factor to job satisfaction 46 and that ameliorates the effects of family stress. 47 Several studies indicate that personal resources buffer job demands, specifically resilience predicts greater psychological well-being in healthcare workers. 48 Resilience has a positive effect on work engagement and communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…2 Resilience, defined as the ability to overcome challenging obstacles and successfully cope with stressful events 45 is a contributing factor to job satisfaction 46 and that ameliorates the effects of family stress. 47 Several studies indicate that personal resources buffer job demands, specifically resilience predicts greater psychological well-being in healthcare workers. 48 Resilience has a positive effect on work engagement and communication skills.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, negative correlations were expected and found between the household conflict subscale and family cohesion and dyadic coping. According to Jiménez‐Picón et al (2021), couples' greater dyadic coping is related to less family conflict. In the same study, couples with conflicting relationships based on negativity showed less cohesion and more hostility in co‐parenting (Jiménez‐Picón et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…According to Jiménez‐Picón et al (2021), couples' greater dyadic coping is related to less family conflict. In the same study, couples with conflicting relationships based on negativity showed less cohesion and more hostility in co‐parenting (Jiménez‐Picón et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marital adjustment can bring many positive outcomes for couples, whereas marital maladjustment can have undeniable negative consequences for their health and relationship. Some studies have shown that marital adjustment has a significant relationship with the health of couples (in terms of sleep quality, stress, and depression level), marital satisfaction, family functioning, and parent-child relationships [4,5].…”
Section: Introductionmentioning
confidence: 99%